The curious case of an internal pilot in a multicentre randomised trial-time for a rethink? - Cook, J; Beard, D; Cook, J; MacLennan, G (BioMed Central, 2016)
Multicentre randomised trials are complex projects with many operational uncertainties. The embedding of a formal check upon study progress and viability at a pre-specified time point (sometimes referred to as an 'internal pilot') is becoming increasingly common within multicentre pragmatic randomised trials. However, it is worth considering this practice. We argue that most, if not all, multicentre trials have reassessment of the recruitment strategy and study processes whilst the study is running. Additionally, we propose discontinuation of the 'internal/external pilot study' terminology. Instead, we suggest for an alternative taxonomy along with greater recognition of the process of refinement which routinely occurs in trials and transparent reporting of it.